The Influence Of Dominant Leadership And Group Cohesiveness On Groupthink Phenomenon In The Decision-Making Process: A Systematic Literature Review - Edi Priyanto; Nur Wening (Green Publisher Indonesia, 2024)
In collective decision-making, a phenomenon known as